Robust nano-fabrication of an integrated platform for spin control in a tunable microcavity - Stefan Bogdanović; Madelaine S. Z. Liddy; Suzanne B. van Dam; Lisanne C. Coenen; Thomas Fink; Marko Lončar; Ronald Hanson (APL Photonics, 2017)
Coupling nitrogen-vacancy (NV) centers in diamonds to optical cavities is a promising way to enhance the efficiency of diamond-based quantum networks. An essential aspect of the full toolbox required for the operation of these networks is the ability to achieve the microwave control of the electron spin associated with this defect within the cavity framework. Here, we report on the fabrication of an integrated platform for the microwave control of an NV center electron spin in an open, tunable Fabry–Pérot microcavity. A critical aspect of the measurements of the cavity’s finesse reveals that the presented fabrication process does not compromise its optical properties. We provide a method to incorporate a thin diamond slab into the cavity architecture and demonstrate the control of the NV center spin. These results show the promise of this design for future cavity-enhanced NV center spin-photon entanglement experiments.